AN ASSESSMENT OF THE SHARE OF REAL ESTATE TAX REVENUES IN THE BUDGET REVENUES OF SELECTED POLISH CITIES FROM 2018-2021 - Cezary Szydłowski (Polityki Europejskie, Finanse i Marketing)
The publication aimed to assess the share of property tax revenue in the overall budget revenues of Poland’s 14 largest cities with populations over 200,000. Property tax rates were also assessed. Property tax is one of the key local taxes collected by the local government. The assessment was carried out using the analytical method, inference method, source document research method, and a literature review. The results of the study indicate that property tax revenues, depending on the city, accounted for between 6.31% (in Warsaw) and 13.98% (in Gdańsk) of the share in total revenues to the city budget. On average, it can be concluded that the real estate tax accounts for ap- proximately 9% of the total income in the budget of the largest cities in Poland. It has also been established that the level of revenue depends on the tax rates. In addition, it was found that there is significant variation between Poland’s largest cities in the share of property tax revenue in total budget revenue.